Gasto público estadual e desenvolvimento: uma análise da capacidade fiscal do estado do Maranhão entre 2002 e 2014 - SANTOS, Marcelo de Sousa (2018)
The objective of this dissertation is to analyze the Fiscal Capacity of the State of Maranhão between 2002 and 2014, having as parameter the analysis of indicators, such as: Fiscal Autonomy (IA), Demand Activation Capacity Indicator - I-CAD, Current Savings and Indebtedness. Linked to this, we will analyze, a priori, the predominant theories of economic thought, as well as the role of the State in the economy, in an attempt to evaluate the Fiscal Capacity in Maranhão. Preliminary results show that the Fiscal Capacity of the entity is presenting difficulties on behalf of the Union, imposing debt payments (on a continuous basis) and increasing expenses with Personnel, Costing (Other Current Expenses) and Investments, despite the good economic activity that (Tax Revenue and Current Transfers), due to its socioeconomic context (primary export), linked to a predominantly urban population, in which 75% of the average income of a maximum of two minimum wages and a significant part of this is on the poverty line.